Influence of palaeoenvironmental factors on the encystment of Cretaceous dinoflagellate cysts (Ceratiaceae): a study from Godavari Graben, Southern India - Masure, Edwige; Jha, Neerja; Duarte, Sarah Gonçalves; Aggarwal, Neha; Arai, Mitsuru [UNESP]; Joshi, Harinam (Taylor & Francis, 2017)
Muderongia staurota forms with long appendages at the distal end of the apical, lateral and antapical horns have been recovered from the Lower Cretaceous Gangapur Formation of Upper Gondwana sequence from the Chintalapudi Sub-Basin (India). The number of distal appendages reflects the number of plates forming the horns. We include these forms in the new species Muderongia gangapurensis sp. nov. The dinoflagellate cysts recovered suggest a late Berriasian to Valanginian for the lower part and a Hauterivian/Barremian age for the upper part of the studied interval of MJR-11 borehole. Unusual Muderongia and Odontochitina cysts bearing similar long appendages have only occasionally been described or illustrated in the literature from sediments rich in continental organic matter. We suggest that Cretaceous Ceratiaceae bearing such appendages are cysts of thecae that encysted in particular environments, where light, salinity, temperature and chemistry of water masses might have been key to their development. Our conclusion is supported by the high morphological variability of horns in modern Ceratiaceae, which reflects environmental factors. We discuss the plasticity of horns in the fossil record and note that such plasticity is recurring in Ceratiaceae, at least in the Early Cretaceous (145 Ma).
Keywords: Ceratiaceae; Cretaceous; Dinoflagellate cysts; India; Muderongia